(untitled) (International Journal of Engineering and Computer Science, 2017)
Aiming at Docker currently only support queries for performance monitoring and logging services for a single container, the performance monitoring and log service scheme in distributed platform are designed and we also conduct test and analysis on it, so that the Docker container cluster can be monitored as a whole. The application of the Docker cloud platform is more stable and optimized, and the integrated management of complex logs is realized. The final result has certain guiding significance to the integration and perfection of Docker platform service.